Chemoenzymatic synthesis of tumor-associated antigen N3 minor octasaccharide. Issue 8 (21st November 2016) - Han, Zhipeng; Chen, Congcong; Meng, Caicai; Gao, Tian; Peng, Peng; Chen, Xi; Wang, Fengshan; Cao, Hongzhi
GRAPHICAL ABSTRACT: ABSTRACT: A highly efficient chemoenzymatic approach was developed for the preparative scale synthesis of complex tumor-associated antigen N3 minor octasaccharide. The success of this approach relies on the highly efficient one-pot multi-enzyme based sequential enzymatic elongation of a chemically synthesized branched tetrasaccharide core structure.